2009
DOI: 10.1155/2009/681270
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of the Ruthenium Complex KP1019 in Models of Mammary Cancer Cell Migration and Invasion

Abstract: The effects of indazolium trans-[tetrachlorobis(1H-indazole)ruthenate(III)] (KP1019, or FFC14A), the second ruthenium compound that entered clinical trials, in an in vitro model of tumour invasion and metastasis show that the antitumour effects of this compound might include also the modulation of cell behaviour although its cytotoxicity appears to be predominant over these effects. The comparison with its imidazole analogue KP418 shows however its superiority, being able to control in vitro cell growth and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
(23 reference statements)
1
24
1
Order By: Relevance
“…Another possible explanation for increased cytotoxicity in vivo is albumin-mediated uptake [54,55]. Previous studies regarding the anti-invasive activity of rutheniumbased compounds revealed certain anti-invasive activity of [38]. Our results, however, could not demonstrate anti-invasive activity of KP1339, neither in the transwell nor in the spheroid-based assays.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Another possible explanation for increased cytotoxicity in vivo is albumin-mediated uptake [54,55]. Previous studies regarding the anti-invasive activity of rutheniumbased compounds revealed certain anti-invasive activity of [38]. Our results, however, could not demonstrate anti-invasive activity of KP1339, neither in the transwell nor in the spheroid-based assays.…”
Section: Discussioncontrasting
confidence: 89%
“…4b). While a related compound investigated previously [38] caused significant reduction of cell migration and invasion in breast cancer cell lines, the ruthenium complex KP1339 had no anti-invasive activity in the models applied here. KP1537 and oxaliplatin, with significant activity in the transwell assay, were inactive in the spheroid invasion assay.…”
Section: Anti-invasive Activity In Spheroid Model and Transwell Assaymentioning
confidence: 61%
“…[21][22][23][24] A number of Ru complexes have been designed and their anti-metastasis activities against various tumours have been investigated extensively. [25][26][27] For example, NAMI-A 28,29 and KP1019 30 have entered phase II clinical studies as NAMI-A can selectively reduce tumour metastasis and inhibit tumour cell invasion in vitro and KP1019 can inhibit the migration and invasion of MDA-MB-231 breast cancer cells by reducing the release of the extracellular matrix (MMP-2/9). In addition, the Ru complex RM175 also exhibits tumour metastasis inhibition and reduces the invasion and metastasis by promoting cell-cell readhesion and by decreasing the release of metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a lack of suitable trans ruthenium derivatives due to the propensity of the molecules to undergo isomerisation. The first reported cytotoxic trans ‐ruthenium complexes were KP1019 ( g ) and NAMI‐A ( h ), which in Phase I clinical trials were well tolerated showing only limited side‐effects . NAMI‐A has also undergone Phase II clinical studies in combination with gemcitabine, however, this combination had some adverse toxicity and failed to show any improvement in results compared with gemcitabine treatment alone .…”
Section: Introductionmentioning
confidence: 99%